(untitled) - Eggeling, Lothar (Boca Raton, 2005)
Handbook of Corynebacterium glutamicum is a comprehensive source of scientific and technical information required for the manipulation and processing ofC. glutamicum, the bacterium used for the production of primary metabolites. The most comprehensive book on the subject, it summarizes the current knowledge in the field ofC. glutamicum research and provides a basis for future work. Written by experts from industry and academia, the book covers all major aspects of C. glutamicum: production, physiology, biochemistry and genetics.
Keywords: Corynebacterium glutamicum,Glutamic acidc,Amino acids; Handbooks, manuals, etc,Glutamic acid,Hiotechnology,Handbooks, manuals, etc,Biotechnology,Handbooks, manuals, etc